Cross-Sectional Association Between Employment Status and Self-Rated Health Among Middle-Aged Japanese Women: The Influence of Socioeconomic Conditions and Work-Life Conflict - Honjo, Kaori (J Epidemiol, 2020)
BACKGROUND: Few studies examining the impact for women of employment status on health have considered domestic duties and responsibilities as well as household socioeconomic conditions. Moreover, to our knowledge, no studies have explored the influence of work-family conflict on the association between employment status and health. This research aimed to investigate the cross-sectional associations between employment status (regular employee, non-regular employee, or self-employed) with self-rated health among Japanese middle-aged working women. METHODS: Self-report data were obtained from 21,450 working women aged 40–59 years enrolled in the Japan Public Health Center-based Prospective Study for the Next Generation (JPHC-NEXT Study) in 2011–2016. Multivariate odds ratios (ORs) and 95% confidence intervals (CIs) were calculated for poor self-rated health (‘poor’ or ‘not very good’) by employment status. Sub-group analyses by household income and marital status, as well as mediation analysis for work-family conflict, were also conducted. RESULTS: Adjusted ORs for the poor self-rated health of non-regular employees and self-employed workers were 0.90 (95% CI, 0.83–0.98) and 0.84 (95% CI, 0.75–0.94), respectively, compared with regular employees. The identified association of non-regular employment was explained by work-family conflict. Subgroup analysis indicated no statistically significant modifying effects by household income and marital status. CONCLUSION: Among middle-aged working Japanese women, employment status was associated with self-rated health; non-regular employees and self-employed workers were less likely to report poor self-rated health, compared with regular employees. Lowered OR of poor self-rated health among non-regular employees may be explained by their reduced work-family conflict.